Disaggregating China's local political budget cycles: "Righting" the U. (February 2019) - Vortherms, Samantha A.
Highlights: Welfare spending varies both across time and space in Chinese municipalities. National reforms increased incentives for welfare spending for local leaders. Welfare spending increased when local leader promotion is not likely. Political budget cycles are more dynamic in Western provinces. Abstract: What impact does spending time horizon have on political budget cycles? While traditional political budget cycles increase visible spending with immediate gains before political turnover, I hypothesize that spending in categories with less-immediate gains categories increases when opportunity costs are lower. In this article, I build on existing literature on budget cycles in both democracies and non-democracies to disaggregate types of budget cycles: those with long-run versus short-run benefits. In China, after central-level reforms, welfare targets, with long-run gains, became visible to local leaders' constituents, the central leaders above them. Local leaders then had an incentive to provide welfare, but only when it was the least costly in terms of opportunity costs. Using fixed-effects models panel data from China's 333 municipalities for 1994–2012, I find welfare spending minimizes both relatively and absolutely around year three, and maximizes at the beginning and end of a politician's tenure, when opportunity costs and probability of political advancement are lowest. These cycles are the most dramatic in western provinces, where education is a particularly important tool for ideological spread. Health and Social Security spending also see expansion at the end of mayor's tenures, although the cycles are less pronounced than in education spending. This study expands the literature on political budget cycles by disaggregating government spending and considering the impact of timeliness on cycles.